Microtubule-Associated Protein 2 Expression in Canine Glioma - Demeter, Elena Alina; Frank, Chad; Rissi, Daniel R.; Porter, Brian F.; Miller, Andrew D. (Frontiers in Veterinary Science, 2019)
Canine glioma is considered a potential model for human glioma, with recent studies of occurrence, therapy, and reclassification supporting the value of the canine model. The current diagnosis of canine glioma is based on morphologic criteria and immunohistochemistry (IHC), including oligodendrocyte transcription factor 2 (Olig2), glial fibrillary acidic protein (GFAP), and 2′, 3′ cyclic nucleotide phosphatase (CNPase). Microtubule-associated protein 2 (MAP2) is a proven marker of human glioma and is used to complement the diagnosis and its specific immunoreactivity pattern contributes to the differentiation of astrocytomas from other glial tumors. The objective of this study was to evaluate whether canine gliomas express MAP2 and to explore differences in the pattern of immunolabeling between different gliomas. Seventy-eight cases of canine glioma were evaluated for MAP2 expression by immunohistochemistry. A glial origin was supported by Olig2 IHC in all cases. MAP2 immunolabeling was evaluated on a semi-quantitative basis, including the percentage of immunolabeled neoplastic cells, as well as the signal intensity, distribution, and pattern of immunolabeling. MAP2 was expressed in all cases, with significant correlation between diagnosis and signal intensity (P=0.04). MAP2 immunolabeling distribution was dominated by diffuse (34/78; 44%), followed by patchy (20/78; 26%), multifocal to coalescing (16/78; 21%), and scattered (8/78; 10%). All oligodendrogliomas (53/53; 100%) and undefined gliomas (12/12; 100%) revealed a combination of perinuclear and cytoplasmic immunolabeling, and all but 3 astrocytomas had a combination of perinuclear and cytoplasmic processes immunolabeling (10/13; 77%). Significant correlation between immunolabeling pattern and diagnosis was obtained (P=0.001). The study demonstrates that MAP2 is expressed in canine gliomas and the pattern of expression can also be applied to help distinguish astrocytomas from oligodendrogliomas and undefined gliomas.